FENOLOGIA DA ANDIROBA (Carapa guianensis, Aubl., MELIACEAE) NO SUL DO ESTADO DE RORAIMA - Maria Rutinéia Nobre Pereira (Ciência Florestal, 2012)
This work was carried out in order to study the phenological pattern of Andiroba in natural forest located in the south of Roraima state, seeking to relate the frequency of phenol-phases occurrence with the rain rate in this period. For the phenological survey 20 adult trees were selected in a permanent sample plot of 9ha. The visits to phenological observations occurred fortnightly from February 2006 to December 2008, recording the presence or absence of flowering, fruiting and leaf change events for each tree. The Spearman correlation was used for analyzing the influence of rainfall on phenology and, the index of synchrony of population (Z) was used for estimating the synchrony of phenological events. The flowering of Andiroba showed to be sub-annual, synchronous and was negatively correlated with the rainfall during the phenological event. Two cycles of flowering were observed: a long one from October until next year, which lasts about nine months, and a short one lasting two months, from July to August. The fruiting is annual, long and synchronous and it was positively correlated with rainfall. The ideal time for collecting ripe fruits at the study site is during the rainy time, that is, from April to July. The leaf flushing was continuous and did not correlate with the rainfall. It was noticed a higher proportion of trees falling leaves between August and November, which characterizes a period of transition between the dry and the rainy period with sensitive reduction of rainfalls.